Digital Storytelling for Historical Understanding: Treaty Education for Reconciliation - Hildebrandt, Katia; Lewis, Patrick; Kreuger, Claire; Naytowhow, Joseph; Tupper, Jennifer; Couros, Alec; Montgomery, Ken (sowi-online e.V., Bielefeld, 2016)
This paper presents the findings of a research project that sought to interrogate the possibilities of digital storytelling as a pathway towards a more complete understanding of treaties and the treaty relationship in western Canada. This research is situated in the province of Saskatchewan, where treaty education (that is, education about the history of the numbered treaties signed between First Nations people and the British Crown, as well as the subsequent history of the treaty relationship) has been mandatory for almost a decade. The paper details a two-year journey alongside elementary educators as they used digital storytelling to take up treaty education in their classrooms. We present an overview of the research project as well as the narratives of a teacher, a researcher, and a Cree knowledge keeper, all of whom were involved in and reflected on the research journey. We consider the research findings alongside these narratives in order to explore the possibilities that digital storytelling might offer as we, as a Canadian nation, move towards reconciliation with Aboriginal people within a Canadian context of ongoing colonialism. Questo articolo presenta i risultati di un progetto di ricerca che ha cercato di indagare sulle possibilità della narrazione digitale di storie (storytelling) come percorso verso una comprensione più completa dei trattati e del rapporto fra i trattati nel Canada occidentale. Questa indagine è situata nella provincia di Saskatchewan, dove l'istruzione sui trattati (cioè, l'educazione sulla storia dei trattati numerati firmati tra la Prima Nazione e la Corona Britannica, così come la storia successiva del rapporto fra i trattati) è stato obbligatorio per quasi un decennio. Il saggio riporta un percorso di due anni con insegnanti di scuola elementare che hanno usato lo storytelling digitale per fare l'educazione ai trattati nelle loro classi. Presentiamo una panoramica del progetto di ricerca ed i racconti di un insegnante, di un ricercatore, e un guardiano Cree della conoscenza, i quali sono stati coinvolti nella ricerca e riflettono sul percorso svolto. Consideriamo i risultati dell’indagine insieme a questi racconti, al fine di esplorare le possibilità che la narrazione digitale potrebbe offrire dato che noi, come nazione canadese, procediamo verso la riconciliazione con gli aborigeni in un contesto canadese di colonialismo in corso. : JSSE - Journal of Social Science Education, 1-2016 Digital Tools and Social Science Education